Direct local solvent probing by transient infrared spectroscopy reveals the mechanism of hydrogen-bond induced nonradiative deactivation. Issue 7 (22nd May 2017) - Dereka, Bogdan; Vauthey, Eric
Abstract : The hydrogen-bond induced quenching of an excited chromophore is visualised by probing O–H vibrations of the interacting solvent molecules. Abstract : The fluorescence quenching of organic dyes via H-bonding interactions is a well-known phenomenon. However, the mechanism of this Hydrogen-Bond Induced Nonradiative Deactivation (HBIND) is not understood. Insight into this process is obtained by probing in the infrared the O–H stretching vibration of the solvent after electronic excitation of a dye with H-bond accepting cyano groups. The fluorescence lifetime of this dye was previously found to decrease from 1.5 ns to 110 ps when going from an aprotic solvent to the strongly protic hexafluoroisopropanol (HFP ). Prompt strengthening of the H-bond with the dye was identified by the presence of a broad positive O–H band ofHFP, located at lower frequency than the O–H band of the pure solvent. Further strengthening occurs within a few picoseconds before the excited H-bonded complex decays to the ground state in 110 ps. The latter process is accompanied by the dissipation of energy from the dye to the solvent and the rise of a characteristic hot solvent band in the transient spectrum. Polarization-resolved measurements evidence a collinear alignment of the nitrile and hydroxyl groups in the H-bonded complex, which persists during the whole excited-state lifetime. Measurements in other fluorinated alcohols and in chloroform/HFP mixtures reveal that the HBIND efficiency depends not only on the strength of the H-bond interactions between the dye and the solvent but also on the ability of the solvent to form an extended H-bond network. The HBIND process can be viewed as an enhanced internal conversion of an excited complex consisting of the dye molecule connected to a large H-bond network.